Tribes, Trade, and Towns: A New Framework for the Late Iron Age in Southern Jordan and the Negev - Bienkowski, Piotr ca. 20./21. Jh. (Bulletin of ASOR, 2001)
Recent research on the Transjordanian Iron Age kingdoms stresses their tribal nature, involvement in the Arabian trade, regional variation, and the mixture of pottery traditions. To determine how this system functioned in southern Jordan (Edom) and the Negev, 19th-century ethnographic data from the same area is used to derive a model of how different tribal groups interacted. The model is based on five aspects: territory and movement, trade, interaction with a gateway town, relationship to central government, and relationship with an imperial power. It is proposed that this model can be appropriately applied to the late Iron Age in southern Jordan and the Negev. Edom was composed of largely independent tribes connected by bonds of allegiance, who interacted with others from Arabia, the Negev, and the west, and controlled the trade among Arabia, Edom, the Beersheba Valley, and Gaza. Certain towns on this route were gathering places for such groups or centers controlling Assyrian interests in the Arabian trade.